Development Of Motion Virtual Laboratory (Movil) Module And Its Effect On The Achievement In The Topic Of Speed And Acceleration Among Form Two Students - Rosli, Asmahwati (2023)
This study aimed at developing the Motion Virtual Laboratory (MoViL) module on the topic of speed and acceleration for form two students. The Design and Development Research methodology as introduced by Richie and Klein (2007) was used in this study.